O Bairro Reforma Agrária e seu Processo de Transformação. Uma revisão da pesquisa de Larissa Mies Bombardi - Santos, Larissa Porto dos (Universidade Federal de São Carlos, 2015)
In 2001, Larissa Mies Bombardi performed a case study regarding the Agrarian Inspection Law, and more specifically the Capivari agrarian core, founed in the 1960s and that became a rural neighborhood. The present paperwork seeks a reviewing of this case study in order to approach the economic and cultural changes expressed through spacial transformations that took place between 2001 through 2015. The goal consisted in understanding the farming production processes in this core and the trasnformations ocurred since Bombardi's study, upon the concept of reproducting peasantry, of the peasants as a reproducting unit. For the conceiving of this work, first and foremost, a study of Larissa Bombardi's “O Bairro Reforma Agrária e o processo de territorialização camponesa” took place, hence the book was taken as primary reference. After, there was the accomplishment of field research, with numerous interviews held with different profiles of local dwellers. Beyond that, the discussion regarding the changes and transformations that took place since Bombardi's study and the neighborhood and the peasantry's current situation, as of 2015. After that, there's a reflection concerning education in rural schools with a singular perspective that englobes the peasant reality. Thus, it's concluded that the peasantry's deal shows it's modifications and adaptations as they happened through the years, given the numerous difficulties regarding their reproduction, as well as “mechanisms” adopted for survival and continuity of this class as expressed by the different dweller profiles compiled in this paperwork. Furthermore, it's concluded that such cultural and social modifications impact directly in the neighborhood's configuration.
The Agrarian Reform Neighborhood and its Transformation Process. A Review of Larissa Mies Bombardi's Research
Keywords: Camponês; Bairro Rural; Reforma Agrária; Peasant; Rural neighborhood; Agrarian Reform; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA AGRARIA